THE RELATIONSHIP OF TEACHERS’ EMOTIONAL INTELLIGENCE TO STUDENT DISCIPLINE - Ming Kiri; Wahyuni Eka Putri; Dara Vann (International Journal of Educatio Elementaria and Psychologia, 2025)
Student discipline is a critical factor in creating an effective learning environment, and it is often influenced by the teacher’s ability to manage classroom dynamics. Teachers’ emotional intelligence (EI) is increasingly recognized as a key competency in this regard. This study aimed to determine the quantitative relationship between the emotional intelligence of teachers and the level of discipline among their students. A quantitative correlational research design was implemented with a sample of elementary school teachers and their students. Teacher EI was measured using a validated Emotional Intelligence Questionnaire, while student discipline was assessed through a standardized discipline scale completed by trained observers. The data were analyzed using Pearson correlation. The results indicated a significant and strong positive correlation (r = 0.82, p < 0.01) between teachers’ emotional intelligence and student discipline levels. Teachers with higher EI scores consistently managed classrooms with higher levels of student discipline. This study concludes that a teacher’s emotional intelligence is a significant predictor of student discipline. Therefore, fostering EI through targeted professional development is a crucial strategy for improving classroom management and creating a more conducive learning atmosphere.